Identification of Bottlenecks in the Plant Life Cycle for Sustainable Conservation of Rare and Endangered Species - Aronne, Giovanna (Frontiers in Ecology and Evolution, 2017)
Long term survival of a species relies on maintenance of genetic variability and natural selection by means of successful reproduction and generation turnover. Although basic to monitor the conservation status of a plant species, life history data are rarely available even for threatened species due to the gap between the large amount of information required and the limits in terms of time and available economic resources to gather these data. Here, the focus on bottlenecks in life-cycle of rare endangered plant species is proposed as a resolving approach to address the challenges of feasible conservation actions. Basic considerations for this approach are: a) all biological and ecological studies on plant species can be scientifically important, but not all of them are equally relevant to conservation planning and management requirements; b) under a changing environment, long term survival of a species relies on generation turnover; c) for conservation purposes, priority should be given to studies aimed to focus on bottlenecks in the succession of generations because they prevent, or slow down natural selection processes. The proposed procedure, named SHARP (Systematic Hazard Analysis of Rare-endangered Plants), consists of a preliminary survey of the already available information on the species and two main components. The first component is the identification of the bottlenecks in the life cycle by means of field surveys. The second is the diagnosis of the causes of the bottleneck by appropriate experimental methods. The target is to provide researchers, managers and practitioners with substantiated indications for sustainable conservation measures.